Comprehensive evaluation of heavy metals in surface water of the upper Banar River, Bangladesh - Tamanna, Tanzin; Tonni, Sofiqunnessa; Shammi, Rifat Shahid; Khan, Md Mehedi Hasan; Islam, Md Sirajul; Hoque, Mir Md Mozammal; Meghla, Nowara Tamanna; Kabir, Md Humayun (International Journal of Agricultural Research, Innovation and Technology, 2023)
The main focus of the research was to examine the dispersion of elements and evaluate the possible ecological impact of heavy metals in the water of the Upper Banar River. To achieve this, water samples were obtained from ten different locations along the river, and the concentrations of Cr, Ni, Cu, Cd, Pb, and As were analyzed using an atomic absorption spectrophotometer (AAS). Results exhibited that the abundance of Cr, Ni, Cu, Cd, Pb, and As in water varied from 1.10 to 3.20, 0.11 to 1.30, 1.30 to 13.50, 1.14 to 1.91, 0.39 to 0.75 and 1.44 to 2.56 µgL-1, respectively. Mean (±SD) concentrations of considered metals declined with the following downward direction: Cu (5.07±4.11) > As (1.94±1.15) > Cr (1.81±0.63) > Cd (1.42±0.23) Pb (0.55±0.12) > Ni (0.54±0.41), indicated that concentrations were reasonably assorted throughout the observed region. Moreover, the Upper Banar River water was contaminated with heavy metals, but the pollution level was not significant based on HPI analysis. Based on the computed HEI values, water quality is deemed low hazard and lower degrees of contamination. Overall, the river's water was still in good condition and had low levels of contamination, as per PI and CD ratings. Upper Banar River water's computed ERI ranged from 7.24 to 12.16, which showed a low-risk level. The study concluded that the Upper Banar River experienced some metallic pollution because of anthropogenic disturbances. Thus, responsible authorities should immediately implement appropriate management strategies and conduct routine water quality monitoring. Int. J. Agril. Res. Innov. Tech. 13(1): 110-122, June 2023